PEMANFAATAN LAYANAN SMS PADA PONSEL UNTUK APLIKASI E-MAIL - Utomo, Pringgo Budi; Zahra, Ajub Ajulian; Isnanto, R. Rizal (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
Abstract The development of technology has replaced manual system into automation system. In telecommunications sector, there is an e-mail (electronics mail) that replaces the common letter which is previously sent through the Post Office. The use of e-mail is more effective because it is more faster. Today Internet users are getting increasingly so the Internet connection becomes slow. For a fast Internet connection requires a payment that is relatively expensive to internet service providers, so that the process of sending and receiving e-mail in any time or in realtime is quite difficult. Based on the fact above, this research was done to develop an application that utilizes short message service on a phone that is used for e-mail applications. This application runs on a computer that functions as a server. A modem ,that is connected to a server, is used for the process of receiving and sending SMS to the destination mobile number. Internet connection using a LAN internet connection to get stablity and fast internet connection. Mobile phones sending e-mail just by sending SMS that accordances with the format to the server, then the server will upload the contents of that SMS to e-mail destination. When there is incoming e-mail at the registered e-mail account in the system, automatically e-mail content will be downloaded by the system and will send to the account e-mail owner's phone number. The process of sending and receiving e-mail on phone is done by using the short message service, because Internet connection process only occurs on the server. From the test results, it is obtained that average delay result is at least 33.1 seconds for delivering more than 600 characters. Sending an e-mail from phone to gmail.com is 10 seconds, faster than shipments to yahoo.co.id (14.6 seconds). From these test results concluded that the use of different mobile number does not affect the sending and receiving SMS between users and systems, as well as SMS messages to the inbox system will not be processed if the wrong SMS format and not from registered users. Keywords: E-mail, SMS, Internet, phone cellular